Spremembe stališč dijakov do oseb z duševno motnjo v času praktičnega pouka v psihiatrični bolnišnici - Pikovnik, Elizabeta (Obzornik zdravstvene nege, 2008)
Introduction: The aim of the article is to present the opinions of the students of Srednja Zdravstvena šola Ljubljana on mentaL patients. The research was carried out with 64 students of Srednja Zdravstvena šola Ljubljana who attended the fourth grade in the school year 2006/07. Methods: For this purpose, three questionnaires were used, which were applied in the research of Mohr, Spiessl and Pichtner in 2005: a questionnaire on prdor knowledge (FVPP), which refers to the prior knowledge of the students of nursing care connected to psychiatry; a questionnaire on practical experience in psychiatry (FEPP), which refers to the direct experience of students while performing practical work at the departments of psychiatry; the questionnaire ATP 35 (Attitudes Toward Psychiatry), which includes different opinions on psychiatry and psychotherapy. The data were processed quantitatively and divided according to frequency. We found the arithmetic mean and measure of dispersal on the basis of this division. In order to test the theoretical model, we applied a correlation analysis. Results: The results were the following: the students' opinions about psychiatry were already positive before their practical work at the 17niversity Psychiatric Hospital Ljubljana.The introduction of practical experience influenced the students' opinions. There was a significant increase in those students who were willing to become a (fe)male nurse in psychiatry. At the same time there was a significant change in opinion regarding the item: `The course Nursing patientswith mental disorders contributes to understanding patients who have internal diseases and surgical patients'. Discussion: During their practical work, students eagerly listened to patients, they did not have any difficulties in beginning conversations, nor did they feel threatened by patients. (Abstract truncated at 2000 characters)
Keywords: Adolescenca; Adolescence; ankete; Attitude; dijaki; duševni bolniki; Education, Nursing; Izobraževanje, zdravstvena nega; Odnos; praktični pouk; Psihiatrična nega; psihiatrija; Psychiatric Nursing; psychiatry and clinical psychology; Questionnaires; Schools, Nursing; stališča; Šole sestrske